Pengaruh Ownership dan Faktor lainnya terhadap Nilai Perusahaan - Effendi, Susanti E; Siahaan, Magda (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
This research examines the effect of return on asset, debt-to-asset ratio, current ratio, firm size, dividend payout ratio, managerial ownership, and institutional ownership on the firm value in non-financial companies listed on the Indonesia Stock Exchange. This research used samples from non-financial companies listed on Indonesia Stock Exchange and purposive sampling to get non-financial companies listed on Indonesia Stock Exchange from 2019 to 2021; 59 companies and 177 data were selected as this research sample. This research shows that the return on asset and debt-to-asset ratio positively affect the firm value. In contrast, the current ratio, firm size, dividend payout ratio, managerial ownership, and institutional ownership do not affect the firm value.